Ecopedagogic: The Influence of Geography Learning On Environmental Care Attitudes - Pranichayudha Rohsulina (International Journal of Science and Environment (IJSE), 2026)
Environmental problems are closely related to low levels of environmental awareness and attitudes. Students’ environmental care attitudes are influenced by educational processes, particularly Geography learning, which integrates ecological and spatial perspectives. This study aims to analyze the influence of Geography learning on students’ environmental care attitudes. The research employed a quantitative approach using a simple linear regression model with a sample of 41 students. Data were collected through questionnaires, interviews, and documentation. The novelty of this study lies in integrating ecopedagogic perspectives into Geography learning to strengthen environmental care attitudes among high school students. The results show that Geography learning has a significant positive effect on environmental care attitudes, with a correlation coefficient of 0.516 and a coefficient of determination of 26.67%. This indicates that improving the quality of Geography learning contributes to enhancing students’ environmental awareness and attitudes.